2000
DOI: 10.21273/hortsci.35.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Cucurbits to the Herbicides Clomazone, Ethalfluralin and Pendimethalin. II. Watermelon

Abstract: Field studies were conducted in 1993, 1994, and 1995 to determine tolerance of seeded and transplanted watermelon [Citrullus lanatus (Thunb.) Matsum and Nak.] to clomazone, ethalfluralin, and pendimethalin using method of stand establishment (directseeded vs. transplanted) and time of herbicide application [preplant soil incorporated (PPI), preplant to the surface (PP), or postplant to the surface (POP)] as variables. Yield and average fruit weight in plots with clomazone wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…Even though growth rates varied greatly between the experiments, the relative difference in clomazone response between genotypes was similar in both environments (Table 3). Variability of tolerance as affected by cucurbit variety compliments previous studies (Boyhan et al, 1995;Cohen et al, 2008;Grey et al, 2000).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Even though growth rates varied greatly between the experiments, the relative difference in clomazone response between genotypes was similar in both environments (Table 3). Variability of tolerance as affected by cucurbit variety compliments previous studies (Boyhan et al, 1995;Cohen et al, 2008;Grey et al, 2000).…”
Section: Resultssupporting
confidence: 87%
“…Boyhan et al (1995) reported that watermelon yields were reduced by clomazone applied PRE at 1.1 kg · ha -1 to direct seeded watermelon. Grey et al (2000) reported that clomazone applied preplant incorporated at 0.84 kg · ha -1 , preplant to the soil surface, and posttransplant to the soil surface caused minor foliar bleaching (14% injury or less), but did not reduce the yields of seeded or transplanted 'Royal Sweet' watermelon. Cohen et al (2008) concluded from a greenhouse study that clomazone applied at 1.0 and 2.0 kg · ha -1 was too injurious to grafted and nongrafted watermelons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Há apenas dois produtos registrados:fenoxaprope-P-etílico e a mistura carfentrazona-etilica + clomazona,que controlam exclusivamente gramíneas (AGROFIT, 2017).Alguns estudos em diversos países mostraram que herbicidas como linuron, trifluralin, butilaty são seletivos para cultura do melão (CANTAMUTO, et al, 1996). E que oclomazonee oxyfluorfen tem potencial de uso no melão (GREY et al, 2000;BELLINDER, et al, 1993).…”
unclassified
“…Boyhan et al (1995) reported that watermelon yields were reduced by clomazone applied pre-emergence at 1.1 and 1.7 kgÁha -1 to direct seeded watermelon. Grey et al (2000) reported that clomazone at 0.84 kgÁha -1 applied preplant-incorporated, preplant to the soil sur-face, and post-transplant to the soil surface caused minor foliar bleaching (14% injury or less) but did not reduce the yields of seeded or transplanted 'Royal Sweet' watermelon. Cohen et al (2008) concluded from a greenhouse study that clomazone at 1.0 and 2.0 kgÁha -1 was too injurious to grafted and non-grafted watermelons to be used safely.…”
mentioning
confidence: 99%